Simulated Heatwaves Lead to Upregulated Chemical Defense of a Marine Foundation Macrophyte Against Microbial Colonizers - Guan, Chi; Saha, Mahasweta; Weinberger, Florian (Frontiers in Marine Science, 2020)
Climate change is characterized not only by increase an mean temperature, but also an increase in the variability around the means causing extreme events like marine heatwaves. These events are expected to have strong influence on the ecology of marine foundation species such as the eelgrass Zostera marina. Bacterial and macroscopic foulers are ubiquitous in the marine environment; they can have detrimental impacts on macrophytes and warming is known to enhance bacterial fouling. Thus, to investigate the consequence of heatwaves on the chemical defence of eelgrass against microbial colonisers, we incubated Z. marina plants in the Kiel Outdoor Benthocosm system under ambient control conditions and two different heatwave treatments: a treatment experiencing two spring heatwaves followed by a summer heatwave, and a treatment only experiencing just the summer heatwave. The capacity to deter microbial colonisers was found to be significantly up-regulated in Z. marina from both heatwave treatments in comparison to Z. marina under control conditions, suggesting defence regulation of Z. marina in response to marine heatwaves. We conclude climate extremes such as heatwaves can trigger an regulation in the defence capacity, which could be necessary for resilience against climate change scenarios. Such dynamics in rapid regulation of defence capacity as found in this study could also apply to other host plant – microbe interactions under scenarios of ongoing climate change or extreme climate events like heatwaves.